Application Of The Expiry Period For The Division Of Joint Property After Divorce Based On The Principle Of Legal Certainty - Nurul Rosida; Heru Kuswanto (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2026)
Abstract Introduction to the Problem: This study aims to determine the statute of limitations on the distribution of joint assets after divorce and the factors that hinder the implementation of the statute of limitations on joint assets after divorce. Purpose/Study Objectives: The application of the statute of limitations on the distribution of joint property after divorce based on the principle of legal certainty, and factors inhibiting the application of the statute of limitations on joint property after divorce. Design/Methodology/Approach: The research method used in this research is normative juridical by taking an approach to the Law. Law (statute approach) and conceptual approach (conceptual approach). Findings: There is a limitation on the period for filing a lawsuit for joint property acquired between husband or wife during the marriage to ensure legal certainty. The obstacles experienced regarding the application of the statute of limitations for joint property lawsuits can occur due to strong local customs, strong cultural influences between communities in each region, and a lack of understanding in the community regarding joint property. Therefore, the way to overcome this is by frequently socializing to provide an understanding to the community regarding what the statute of limitations and joint property are. Paper Type: Research Article